Thermohydrodynamic instability in fluid-film bearings - Wang, Jianke (John Wiley & Sons, 2016)
Thermohydrodynamic Instability in Fluid-Film Bearings aims to establish instability criteria for a rotor-bearing system associated with fluid-film journal bearings.